Characterization of β2-Glycoprotein I Binding to Phospholipid Membranes - Harper, Mark F.; Hayes, Peter M.; Lentz, Barry R.; Roubey, Robert A. S. (Thrombosis and Haemostasis, 1998)
The plasma protein β2-glycoprotein I (β2-GPI) is a major target of autoantibodies in patients with the antiphospholipid syndrome. To understand the physiological function of β2-GPI and its potential role in the pathophysiology of the antiphospholipid syndrome, the binding of β2-GPI to phospholipid membranes was characterized. The interaction of β2-GPI with unilamellar vesicles containing varying amounts of acidic phospholipids with phosphatidylcholine (PC) was measured at equilibrium via relative light scattering. Analysis of binding isotherms gave apparent Kd values ranging from approximately 5.0 to 0.5 μM over a range of 5-20 mol % anionic phospholipid. Inhibition of binding by increasing ionic strength and Ca2+ ions suggests that binding is primarily electrostatic. These data indicate that β2-GPI binding to membranes with physiological anionic phospholipid content is relatively weak in comparison to plasma coagulation proteins, suggesting that β2-GPI does not function as a physiological anticoagulant based on its phospholipid-binding properties.